(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Purpose. To determine the concordance of retinal nerve fiber layer (RNFL) thickness in glaucomatous and normal fellow eyes and also to compare it with normal individuals using optical coherence tomography (OCT). Material & method. An observational cross-sectional study including 73 primary open angle glaucoma cases and 73 normal individuals not having primary open angle glaucoma (POAG) was done. RNFL thickness of both eyes was measured using OCT by fast RNFL thickness protocol. Average RNFL thickness, quadrantic that is inferior, superior, nasal and temporal, and sectoral RNFL thickness was evaluated. The values were compared among the fellow normal eyes and glaucomatous eyes of the same patient and also with the eyes of individuals not having glaucoma. Results. The average RNFL thickness for normal eyes was 90.65±15.04 μm, glaucomatous eyes was 76.83 ± 14.02 μm and fellow eyes of glaucomatous patients was 82.06±14.60 μm. A statistically significant difference was seen both between non glaucomatous and glaucomatous group and also between glaucomatous and fellow eyes of glaucomatous group. (p<0.001) Conclusion. Symmetry of RNFL defects was seen between glaucomatous patients and their fellow eyes corresponding with the pattern of early glaucomatous damage.